K-Band Digital Power Amplifier Based on InP DHBT. Issue 1 (1st September 2022) - Xu, Xindong; Guo, Runnan; Zhou, Guangchao; Zhang, Bin; Tao, Hongqi
Abstract : Based on 0.7- μ m indium phosphide (InP) double heterojunction bipolar transistor (DHBT) process, this paper designs a digital power amplifier (DPA) monolithic microwave integrated circuit. Digital-to-analog converter (DAC), modulation and power amplifier are integrated into the DPA, reducing losses and improving linearity of traditional radio frequency (RF) links. The test results show that the DPA can achieve an output power of 23-23.5 dBm and power added efficiency (PAE) of 21.5-23% within 19.2-21.2 GHz. And the mean squared error of normalized output voltage is 0.0158 at 20 GHz. Then, asymmetrical synthesis technology is used to improve the efficiency of DPA in non-full amplitude state. Simulation results of DPA demonstrate saturated output power of 23.5 dBm and the maximum PAE of 21.9% in 19-21 GHz. At 20 GHz, the PAE between full and half amplitude state is greater than 20%.